Analisis Pengaruh Corporate Governance Dan Pengaruh Keputusan Pendanaan Terhadap Kinerja Perusahaan Perbankan Di Indonesia - M. Syafirqurrahman, Wahyu Andiarsyah, Wahyu Suciningsih (Jurnal Akuntansi, 2014)
The purpose of this study was to determine the effect of corporate governance variable there are the proportion of the board of independent commissioners, the frequency of board commissioners meetings, the frequency of board director meetings.